EFEKTIVITAS MAGGOT BLACK SOLDIER FLY SEBAGAI PENGURAI SAMPAH SAYUR-SAYURAN, SAMPAH BUAH-BUAHAN, DAN SISA MAKANAN TAHUN 2023 - Lindawati, Lindawati; Gameli, Cahyani Rahmi; Wijayantono, Wijayantono; Marza, R. Firwandri; Afridon, Afridon (Media Penelitian dan Pengembangan Kesehatan, 2023)
Organic waste is a type of waste that can rot and decompose again. Most organic waste is thrown into landfills, resulting in piles of rubbish. One way that can be done to reduce damage to the environment and the risk of causing disease is to reuse organic waste by using decomposer animals, namely the Black Soldier Fly or in Latin Hermetia illucens. This research aimed to determine the effectiveness of the Maggot Black Soldier Fly in decomposing vegetable waste, fruit waste and food waste. This research was an experiment carried out for 12 days with 3000 grams of organic waste each. The waste variation uses 3 repetitions using 150 grams of maggot and regular checks are carried out on temperature, pH and humidity. Based on the results of maggot research, maggots' decomposition of vegetable waste increased by 267%. From the results of the ANOVA test, it was found that there was no significant difference in the weight of maggots as decomposers of vegetable waste, fruit waste and food waste. The reduction in waste weight after being broken down by food waste maggots was more effective with a percentage of 72%. In the ANOVA test results it was found that there was a significant difference between vegetable waste and food waste with a Mean Difference (I-J) value of 383,333. It is better for maggots to use food waste when decomposing waste because it has a soft texture, stable pH and humidity, and produces good growth for maggots.